Ultrasound Atherosclerosis Burden Score as a tool for predicting adverse cardiovascular events in patients with various cardiovascular risks aged 40-64 years - V. V. Genkel; A. S. Kuznetcova; L. R. Pykhova; I. I. Shaposhnik (Российский кардиологический журнал, 2022)
Aim. To investigate the prognostic significance of the Atherosclerosis Burden Score (ABS) in relation to the development of major adverse cardiovascular events in patients of different cardiovascular risks (CVR) aged 40 to 64 years.Material and methods. Men and women aged 40 to 64 years were included in the study. All the patients underwent duplex scanning of the carotid arteries and lower limb arteries. The total ABS was calculated by assessing the presence of plaque in the carotid and femoral bifurcations on both sides. The combined endpoint was cardiovascular death, nonfatal myocardial infarction, nonfatal stroke, coronary revascularization, or peripheral artery revascularization.Results. The study included 232 patients who met the inclusion criteria, with a median age of 55,0 years. Very high CVR was established in 94 (40,5%) patients, while high CVR — in 48 (20,7%) patients, and low and intermediate CVR — in 90 (38,8%) patients. The follow-up period lasted 23,6 (15,5; 51,2) months, providing 632,6 patient-years of follow-up. Events within composite endpoint occurred in 28 (12,1%) patients. Increased cumulative risk of adverse cardiovascular events was observed for ABS ≥2, with a significant increase in relative risk (RR) for ABS ≥3. According to Cox regression analysis, ABS 3 was associated with a 3,71-fold (95% CI 1,18-11,6; p=0,025) increase in the RR of adverse cardiovascular events after adjustment for sex, age, baseline CVR, obesity, smoking, diabetes, CAD, a history of myocardial revascularization, type 2 diabetes, drug therapy, and levels of non-high density lipoprotein cholesterol, highly sensitive C-reactive protein, and glomerular filtration rate.Conclusion. In patients of various CVR aged 40-64 years, an ABS ≥3 was associated with a 3,71-fold (95% CI, 1,18-11,6; p=0,025) increase in relative risk of adverse cardiovascular events after adjusting for potential confounders, including sex, age, baseline CVR, CAD, and type 2 diabetes.